Large deviations in the problem of distinguishing the counting processes - Lin'kov, Yu. N. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We prove the general limit theorem on probability of large deviations of the logarithm of the likelihood ratio with the null hypothesis and alternative. Weaker versions of the principle of large deviations are obtained in predictable terms for the problem of distinguishing the counting processes. The case of counting processes with deterministic compensators is studied.